STRATEGI UNIT KONTEN MEDIA BARU TVRI SULAWESI SELATAN DALAM MENGELOLA YOUTUBE (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
This study aims (1) to find out the strategy for the Jokka-Jokka Program at the Fridayanki Event for the new media content unit implemented by TVRI South Sulawesi in managing YouTube. (2) Knowing the obstacles faced by the Jokka-Jokka Program at the Fridayanki Event in live streaming TVRI South Sulawesi's YouTube.The method used is a qualitative research method with a communication science approach, data collection techniques, in-depth interview techniques, observation, and documentation. Data processing and analysis techniques, data reduction, data presentation, and drawing conclusions. The research informants consisted of 7 people, namely 5 new media content unit teams, 2 audiences who accessed live streaming shows or the Jokka-jokka and Jumatanki content programs on YouTube TVRI South Sulawesi to find out the obstacles faced by the new media content team and access content on YouTube.The results of the study showed that the strategy carried out by the Jokka-Jokka Program at the Fridayanki event in managing YouTube, namely the TVRI South Sulawesi new media content team conducted a location survey for shooting. Furthermore, the TVRI South Sulawesi new media content team carried out various live-streaming production processes through social media including YouTube. Then be more productive and innovative in making and taking pictures for the needs of new media content units. Create new media content with an attractive presentation for the audience. Finally did a delayed broadcast for live streaming problems. The obstacle faced by the Jokka-Jokka Program in conducting live streaming on Youtube TVRI South Sulawesi is the lack of sufficient equipment in place. Unstable internet network and limited electricity. Then unravel operational orders for production. The last amount is less.